Dampak Pemekaran Daerah terhadap Struktur Ekonomi Kabupaten Hulu Sungai Utara dan Kabupaten Balangan - Ernawati Lipat Masan; Muhammad Rusmin Nuryadin (PPJP Universitas Lambung Mangkurat, 2020)
Generally, regional expansion is one form of local autonomy and is one of the policies that need to be considered due to regional growth, equitable regional development, and regional development. It can be maximized. The purpose of this study was to determine the impact of the Balangan Regency region expansion from the Hulu Sungai Utara Regency, whether with the division there was a shift in economic structure in the two districts. Several analysis methods are used to answer the problem, namely: Location Quotient Analysis (LQ), Shift-Share Analysis, and Overlay Analysis. The data used in this study are secondary in the form of Hulu Sungai Utara Regency GRDP, Balangan Regency GRDP, and South Kalimantan Province GRDP based on business fields with the base year 2010. The study results based on Location Quotient analysis show that the superior base sector in North Hulu Sungai Regency is parent districts are as many as 12 base sectors.In contrast, in the newly formed districts, there is only one base sector. The calculation result of Shift-Share analysis shows a shift in the two districts' economic structure, namely from the primary industry to the secondary sector. The development of Overlay analysis indicates that there are ten leading sectors in the central districts, and in the newly created communities, there are no top sectors.